Simultaneous detection of glucose, uric acid and cholesterol using flexible microneedle electrode array-based biosensor and multi-channel portable electrochemical analyzer - Gao, Jie; Huang, Wenzheng; Chen, Zhipeng; Yi, Changqing; Jiang, Lelun (Sensors and actuators. B, Chemical, 2019)
[Display omitted] •A flexible microneedle electrode array-based biosensor (MEAB) was fabricated.•A homemade multi-channel portable electrochemical analyzer (MPEA) was developed.•Simultaneous detection of glucose, uric acid and cholesterol was achieved by using MPEA and MEAB. The development of versatile and low-cost biosensor system for rapid and simultaneous detection of multiple blood metabolites is highly demanded for home healthcare. We developed a flexible microneedle electrode array-based biosensor (MEAB) and a multi-channel portable electrochemical analyzer (MPEA) for the simultaneous detection of glucose, uric acid, and cholesterol. Microneedle electrode array (MEA) was fabricated on the flexible substrate using magnetorheological drawing lithography, followed by sputter coated with Au/Ti film. Then, through biofunctionalized with glucose oxidase, uricase and cholesterol oxidase, MEA was conditioned as a biosensor for simultaneous detection of glucose, uric acid and cholesterol. MEAB demonstrated excellent sensing performance with a wide linear range (glucose, 2–12 mM; uric acid, 0.1–1.2 mM; cholesterol, 1–12 mM), low detection limit (glucose, 260 μM; uric acid, 4 μM; cholesterol, 440 μM), and rapid response time (∼4 s). MPEA, a homemade ARM STM32 microcontroller-based electrochemical analyzer, was validated to be comparable to that of the commercial electrochemical workstation. MPEA integrated with flexible MEAB could accurately and simultaneously detect glucose, uric acid, and cholesterol levels in serum, and the results were consistent with the portable electrochemical device. The ease-of-use of the reported biosensor system will facilitate effective monitoring of blood metabolites at home.